Kampanye Mencegah Pemanasan Global Melalui Pengurangan Sampah Plastik di Kolam Retensi Boulevard Kota Kendari - Koodoh, Erens E.; La Ode Aris; Laxmi, Laxmi; Sarlan Adi Jaya; Abdul Jalil (Bengkulu Institute, 2025)
This Community Service (PKM) is intended to provide a comprehensive understanding to the community or young people about the importance of minimizing the reduction of plastic waste because it is very dangerous for the sustainability of human life and environmental sustainability. The methods used in this activity are discussion, question and answer and lectures. The purpose of this service on how to reduce plastic waste among young people in the Boulevard Retention Pool is to raise the feelings and awareness of young people in this area so that they can participate in environmental problems caused by plastic waste. Information obtained from this activity shows that young people are actually aware of the importance of maintaining environmental cleanliness and the dangers of plastic waste, but they are not yet accustomed to implementing a lifestyle without the use of plastic. The evaluation carried out at the end of the activity basically revealed that young people are ready to participate in the activity because it strengthens their desire to protect the environment from the impact of plastic waste, and they are still willing to participate in similar activities.